BthTX-I, a phospholipase A2-like toxin, is inhibited by the plant cinnamic acid derivative: chlorogenic acid - Cardoso, Fábio Florença [UNESP] (2024)
Snakebite is a significant health concern in tropical and subtropical regions, particularly in Africa, Asia, and Latin America, resulting in more than 2.7 million envenomations and an estimated one hundred thousand fatalities annually. The Bothrops genus is responsible for the majority of snakebite envenomings in Latin America and Caribbean countries. Accidents involving snakes from this genus are characterized by local symptoms that often lead to permanent sequelae and death. However, specific antivenoms exhibit limited effectiveness in inhibiting local tissue damage. Phospholipase A2-like (PLA2-like) toxins emerge as significant contributors to local myotoxicity in accidents involving Bothrops species. As a result, they represent a crucial target for prospective treatments. Some natural and synthetic compounds have shown the ability to reduce or abolish the myotoxic effects of PLA2-like proteins. In this study, we employed a combination approach involving myographic, morphological, biophysical and bioinformatic techniques to investigate the interaction between chlorogenic acid (CGA) and BthTX-I, a PLA2-like toxin. CGA provided a protection of 71.8% on muscle damage in a pre-incubation treatment. Microscale thermophoresis and circular dichroism experiments revealed that CGA interacted with the BthTX-I while preserving its secondary structure. CGA exhibited an affinity to the toxin that ranks among the highest observed for a natural compound. Bioinformatics simulations indicated that CGA inhibitor binds to the toxin's hydrophobic channel in a manner similar to other phenolic compounds previously investigated. These findings suggest that CGA interferes with the allosteric transition of the non-activated toxin, and the stability of the dimeric assembly of its activated state.